IDENTIFICATION OF HAZARDOUS CHEMICAL AND MICROBES CONTAMINATION IN FOODS OF STREET VENDORS AROUND IAIN SYEKH NURJATI CIREBON - Azhari, Azmi; Nurjannah, Laita (Jurnal Pendidikan Matematika dan IPA, 2019)
This study aimed at identifying chemical and microorganism contamination in foods of street vendors around Institut Agama Islam (IAIN) Syekh Nurjati Cirebon. The samples are meatball, cilok, grilled fish cake, nuggets, rolade, sauce, crackers, and iced water drinks. The sample tests are formalin test, borax test, Rodhamine B test, Methanyl Yellow test, and Coliform Escherichia coli MPN test. The results showed that some food samples like meatball, cilok, grilled fish cake, nuggets,and rolade were positive of formalin borax contaminated. The iced water drinks are contaminated by Coliform E. coli. The other samples like sauce and crackers  were negative of Rhodamine B Methanyl Yellow contaminated. In conclusion, according to this study, the foods of street vendors at IAIN Cirebon are not yet safe to be consumed.